حوار الرسول صلى الله عليه وسلم مع المشركين من خلال سورة الأنعام: دراسة تحليلية - بنادري، فرزانه بلالي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims to focus on the discussion between the Prophet (peace be upon him) and the polytheists as depicted in Surat Al-An'am. The researcher used an inductive approach by collecting information from both classical and contemporary sources related to this subject. The analytical method was also used to analyze the content related to the subject from various sources and references. This study highlights the discussion between the Prophet (peace be upon him) and the polytheists in this Surah. This discussion views the belief and legislation aspects as well as acts of worship. These aspects have a significant effect in preparing the Dai'yah morally, enhancing his belief and educating him in Fiqh so he can become a strong and smart conversationalist which is one of the highest objectives of Islamic Da'wah. This discussion also focuses on the methods that the Prophet (peace be upon him) used in his discussion with the polytheists. These methods were divided into verbal and practical methods. The verbal methods include the speaking ways that are used by the Dai'yah in his Da'wah which include wisdom, good advice, invitation and intimidation, stories, teaching and stating. Whereas the practical method means the way of Da'wah by acts and behaviours including viewing and meditating upon the signs in the universe, disputes, gradation and intellectual argumentation to prove monotheism. Furthermore, this research views various properties and characteristics like intellectual, spiritual, and behavioural that every Muslim Dai'yah shoul have.